Evaluación de la composición química y actividad antioxidante del aceite de amaranto (Amaranthus hypochondriacus). - Villamarin Álvarez, Josué Michael (2023)
The purpose of this research project was to evaluate the chemical composition and antioxidant activity of amaranth oil (Amaranthus hypochondriacus). For the extraction, an experimental design of surface response was applied in the numerical optimization with the maximum desirability through a linear design with 11 experimental runs at different extraction times (60 min, 105 min, 150 min) and a ratio of plant material with ethanol 100ml + chloroform 400ml (1:4, 1:6, 1:8). In the proximal chemical composition of the seed, the following values were obtained: 62,51% carbohydrate, 14,98% protein, 9,75% moisture , fat 6,11%, fiber 3,86%, and 2,78% ash. The predicted value provided by the Design-Expert software determined that a better performance (6,16867%) would be obtained in a time of 114 minutes with the ratio of one part of plant material and eight parts of solvent (1:8) with a desirability of 1, which corroborates that the established design is optimal. The experimental data was 6,09%, when comparing them, so it can be seen that the predicted one has a higher performance. The liquid gas chromatography (HPLC) detected 13 compounds, linoleic (47,01%), oleic (23,03%), palmitic (19,19%), stearic (3,67%), cis-11,14 ,17- icosatrienoic (1,24%), cis-8,11,14 Eicosatrienoic (1,16%), linolenic (1.15%), cis-10-Heptadecanoic (0,98%), alkyd (0,80%) linolenic (0,55%), cis-11- Eicosenoic (0,54%) palmitoleic (0,40%) and cis-5,8,11,14,17- Eicosapentaenoic (0,29%). Total phenols were determined by FRAP 726,60 µmol Fe2+/g and ABTS 0,34 IC50 4 (mg/ml). Likewise, the physicochemical analysis determined an iodine index of 99,12%, peroxide index 2,21 meqO2/kg, 0,11% m/m of oleic acid and a density of 0,8712 g/ml. The extracted oil was stored in an amber container at 4°C in a dark and cool place. Due to its components, the oil has great potential for agro-industry which can help to minimize or replace chemical additives, innovate its products, and obtain functional foods that will satisfy the needs of the consumer since currently the human being is seeking for healthy foods.